El impacto de algunos factores sociales determinantes de patología mental en Lima Metropolitana - Valdivia Ponce, Oscar (1972)
In a random sample of Lima and Callao the influence of some social factors in mental health was studied. The findings of this research can be sumarized as follows: The internal migration to the metropoli determine in the inmigrant reactions of desadaptation which are manifested during the first contac with the city, with his work and with the interaction in interpersonal relationship. The socio-dynamic impact has influence, as an important variable, in the reactions of desadaptation afeccting them in proportion and intensity according to socio-economic status. The birth place of the population ice studied is an important demographic factor in determining emotional disturbing reactions wich are more frequent as he descend in the socio-economic level. The reactions of emotional disturbance in migrants are higher when the cultural contrast is more intense.